The impact of myocardial fibrosis biomarkers in a heart failure population with atrial fibrillation—The HARVEST-Malmö study - Nezami, Zainu; Holm, Hannes; Ohlsson, Marcus; Molvin, John; Korduner, Johan; Bachus, Erasmus; Zaghi, Amir; Dieden, Anna; Platonov, Pyotr G.; Jujic, Amra; Magnusson, Martin (Frontiers in Cardiovascular Medicine, 2022)
Several studies suggest that circulating biomarkers of myocardial fibrosis are associated with worse prognosis in subjects with atrial fibrillation (AF). Here, we aimed to explore associations between fibrosis biomarkers, prevalent AF and left atrial volume (LAV) enlargement in subjects with heart failure (HF). Additionally, we evaluated the prognostic impact of fibrotc biomarkers in HF with co-existing AF. Patients hospitalized for HF (n= 316, mean age 75 years; 30% women) were screened for AF. Seven proteins previously associated with myocardial fibrosis (metalloproteinase inhibitor 4 (TIMP-4), soluble interleukin 1 receptor-like 1 (ST-2), galectin 3 (GAL-3), growth/differentiation factor 15 (GDF-15) and matrix metalloproteinase 2, 3 and 9 (MMP-3, MMP-3 and MMP-9 respectively)) were analysed using a proximity extension assay. Proteins with significant Bonferroni-corrected associations with mortality and re-hospitalization risk were taken forward to multivariable Cox regression analyses. Further, Bonferroni-corrected multivariable logistic regression models were used to study associations between protein plasma levels, prevalent AF and severely enlarged left atrial volume index (LAVI48 ml/m2). Prevalent AF was observed in 194 patients at hospitalization of whom 178 (92%) were re-hospitalized and 111 (57%) died during the follow-up period. In multivariable logistic regression models, increased plasma levels of TIMP-4, GDF-15 and ST-2 were associated with prevalence of AF whereas none of the seven proteins showed any significant association with severely enlarged LAVI. Increased plasma levels of five proteins yielded significant associations with all-cause mortality in patients with co-existing AF; TIMP-4 (HR 1.33; CI95% 1.07-1.66; p=0.010), GDF-15 (HR 1.30; CI95% 1.05-1.62; p=0.017), GAL-3 (HR 1.29; CI95% 1.03-1.61; p=0.029), ST-2 (HR 1.48; CI95% 1.18-1.85; p<0.001) and MMP-3 (HR 1.33; CI95% 1.09-1.63; p=0.006). None of the proteins showed any significant association with re-hospitalization risk. In this study we were able to demonstrate that elevated levels of three plasma proteins previously linked to myocardial fibrosis, are associated with prevalent AF in a HF population. Additionally, higher levels of five plasma proteins yielded increased risk of mortality in HF population with or without co-existing AF.